The Use of Emotional Language in Communication Between Adolescents in Bandung City: A Psycholinguistic Approach - Iskandar, Ramadhan Attalarik (Penerbit Hellow Pustaka, 2024)
The problem put forward concerns the development of teenagers' use of emotional language in the city of Bandung. This research aims to determine the emotional language in the form of feelings of anger, sadness, fear, enjoyment, love, annoyance, shame, honesty, enthusiasm, desire, and joy. The emotional language theory applied according to Goleman and Sarlito W. Sarwono. The method used is a mixed method by combining qualitative and quantitative descriptive approaches. Data was obtained through an emotional language questionnaire from 42 teenagers. The research results obtained state that the use of emotional language by teenagers in Bandung City has 2 gender classifications consisting of 3 age and phase classifications, then produces 11 types of emotional language categories, namely: anger (2.53%), sadness (17.11 %), fear (6.14%), enjoyment (9.64%), love (7.95%), annoyance (7.23%), shame (5.54%), honesty (6.02%), enthusiasm (17.47%), desire (11.57%), and excitement (8.80%). The conclusion confirms that the emotional language of enthusiasm is most often felt by 42 teenagers in the city of Bandung, giving rise to a positive impression on the Indonesian generation.